2022
DOI: 10.3389/fnins.2022.794653
|View full text |Cite
|
Sign up to set email alerts
|

Ankk1 Loss of Function Disrupts Dopaminergic Pathways in Zebrafish

Abstract: Ankyrin repeat and kinase domain containing 1 (ANKK1) is a member of the receptor-interacting protein serine/threonine kinase family, known to be involved in cell proliferation, differentiation and activation of transcription factors. Genetic variation within the ANKK1 locus is suggested to play a role in vulnerability to addictions. However, ANKK1 mechanism of action is still poorly understood. It has been suggested that ANKK1 may affect the development and/or functioning of dopaminergic pathways. To test thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Ankyrin repeat and kinase domain containing 1 (ANKK1) is a receptor-interacting protein (serine/threonine kinase) that participates in various BP, such as cell survival and tissue differentiation. [ 19 20 ] To the best of our knowledge, no data is available on ANKK1, neutrophils, and atherosclerosis. We deduced that ANKK1 might regulate the survival of neutrophils that participate in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ankyrin repeat and kinase domain containing 1 (ANKK1) is a receptor-interacting protein (serine/threonine kinase) that participates in various BP, such as cell survival and tissue differentiation. [ 19 20 ] To the best of our knowledge, no data is available on ANKK1, neutrophils, and atherosclerosis. We deduced that ANKK1 might regulate the survival of neutrophils that participate in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Genome editing has been used to model human tumors such as liver cancer [ 70 ], paraganglioma [ 71 ], skin melanoma [ 72 ], and epithelioid sarcoma [ 73 ]. Among neurologic diseases, amyotrophic lateral sclerosis [ 74 ], epilepsy [ 75 , 76 , 77 , 78 , 79 ], Hirschprung’s disease [ 80 ], autism [ 81 , 82 , 83 , 84 ], spastic paraplegia [ 85 ], restless legs syndrome [ 86 ], insomnia [ 87 ], microcephaly [ 46 ], neurotransmitter function of dopamine [ 88 ], monoamine [ 89 ], and others [ 90 , 91 ]. Cleft lip and cleft palate mutants also have been tested [ 92 ].…”
Section: Genome Editing In Salmonidae and Cyprinidae Aquaculture Fish...mentioning
confidence: 99%
“…Studies have shown that ANKK1 (ankyrin repeat and kinase domain containing 1) gene variants may be involved in the formation of addictive behavior, possibly by influencing the development and function of the dopaminergic system (Koeneke et al, 2020). A recent study showed a likely functional link between ANKK1 and DRD2 (Leggieri et al, 2022).…”
Section: Dopamine-and Catecholamine-related Signaling Pathwaymentioning
confidence: 99%